Adipocyte‐derived monocyte chemotactic protein‐1 (MCP‐1) promotes prostate cancer progression through the induction of MMP‐2 activity. Issue 10 (27th April 2015) - Ito, Yusuke; Ishiguro, Hitoshi; Kobayashi, Naohito; Hasumi, Hisashi; Watanabe, Masatoshi; Yao, Masahiro; Uemura, Hiroji
<x xml:space="preserve">Abstract</x> BACKGROUND Obesity is known to be associated with prostate cancer development and progression, but the detailed mechanism is not clear. Monocyte chemotactic protein‐1 (MCP‐1) is secreted from cancer cells, stromal cells, and adipocytes, and it is involved in prostate cancer progression. Here we investigated the biological role of MCP‐1 secreted from adipocytes for prostate cancer cells. METHODS Human pre‐adipocytes (HPAds) were cultured and differentiated to mature adipocytes. Conditioned medium (CM) from HPAd cells was obtained using phenol red‐free RPMI1640 medium. We performed a cytokine membrane array analysis to detect cytokines in the CM. To characterize the physiological function of MCP‐1 in the CM, we performed an MTT‐assay, a wound‐healing and invasion assay with anti‐MCP‐1 antibody using three prostate cancer cell lines: DU145, LNCaP, and PC‐3. Matrix metalloproteinase (MMP)‐2 and MMP‐9 activities were evaluated by gelatin zymography. A qPCR and Western blotting were used to examine the mRNA and protein expression levels of MMP‐2. RESULTS The cytokine membrane array of the CM showed a strong signal of MCP‐1compared to the control medium, and we thus focused our attention on MCP‐1 in the CM. The CM up‐regulated the cancer cell proliferation, and the neutralization by anti‐MCP‐1 antibody inhibited the proliferative effect of the prostate cancer cell lines. The CM greatly increased the invasive activity in the prostate cancer cell lines, and anti‐MCP‐1 antibody decreased the invasiveness. Gelatin zymography revealed that the CM markedly enhanced the enzymatic activity of MMP‐2, and anti‐MCP‐1 antibody down‐regulated its effect. MMP‐2 mRNA expression was undetected and the MMP‐2 protein level was unchanged between the control medium and CM in DU145 cells. CONCLUSIONS MCP‐1 from adipocytes enhances the growth and invasion activity of prostate cancer cells. The inhibition of MCP‐1 derived from adipocytes might be an effective treatment for prostate cancer. Prostate 75:1009–1019, 2015. © 2015 Wiley Periodicals, Inc.